Efficacy of an orally administered combination of Lactobacillus paracasei LC11, cranberry and D-mannose for the prevention of uncomplicated, recurrent urinary tract infections in women. Issue 1 (February 2021) - Murina, Filippo; Vicariotto, Franco; Lubrano, Chiara
Background: Most women experience a urinary tract infection (UTI) at least once in their lifetime. The present study determined the efficacy and safety of a combination of Lactobacillus paracasei LC11, cranberry and D-mannose (Lactoflorene Cist ® ) in the prophylaxis of recurrent uncomplicated UTIs in premenopausal women. Methods: This single-centre study enrolled premenopausal women aged 18–50 years with an acute UTI and a history of recurrent uncomplicated UTIs. Patients were first treated with fosfomycin (3 g once a day for 2 days) to eliminate any underlying infection, followed by treatment with Lactoflorene Cist ® once a day for 10 days/month for 90 days (Group 1), Lactoflorene Cist ® once daily for 90 days (Group 2) or no treatment (Group 3; control). The main study endpoint was the rate of UTI recurrence during the study period. Any adverse events with treatment were also recorded. Results: A total of 55 women (mean age 39.3 years; range: 20–46) were enrolled in the study. A significantly higher proportion of patients in the control group experienced UTIs during the study period compared with the two treatment groups (52.9% vs 16.0% in Group 1 and 15.5% in group 2; p < 0.01). Similarly, a higher proportion of patients in Group 1 (65.8%) and Group 2 (68.7%) remained UTI-free during the study versus the control group. No adverse events were reported in the treated patients. Conclusion: Prophylactic treatment with Lactoflorene Cist ® was effective and safe in the management of recurrent uncomplicated UTIs in premenopausal women.